Labour market reforms in brazil (2017-2021): An analysis of the effects of recent flexibilization on labor market legislation - Oreiro José Luis; Gabriel Luciano Ferreira; D’Amato Stefan Wilson; da Silva Kalinka Martins (Panoeconomicus, 2023)
The main objective of this work is to analyze the effects of Brazilian Labor Market Reform (BLMR) in the short run and, based on identified changes in the economy in recent decades, to verify how these changes have affected the labor market. Four methods were used in a complementary way: (i) employment quality index; (ii) panel data estimation method; (iii) synthetic control method and (iv) microdata analysis. We observed that there was no considerable increase in the quality of employment and formal employment and the rate of unemployment did not decrease after the implementation of these changes. Part of this dynamic is cyclical and related to exogenous shocks, such as the COVID pandemic on the Brazilian economy. Finally, according to econometric analysis, the rate of unemployment in Brazil is more responsive to investment rates and the business environment than to unit labor cost and changes in labor legislation.